2023
DOI: 10.3390/molecules28135263
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and ACE-Inhibitory Activity of Protein Hydrolysates Produced from Atlantic Sea Cucumber (Cucumaria frondosa)

Abstract: Atlantic sea cucumber is a benthic marine echinoderm found in Northwest Atlantic waters and is harvested mainly for its body wall. The body wall, along with internal organs and aquaphyrangeal bulb/flower, is a rich source of proteins, where the latter parts are often considered as processing discards. The objective of this research was to produce protein hydrolysates from sea cucumber tissues (body wall, flower, and internal organs) with bioactive properties associated with antioxidants, DNA and LDL cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…In addition, the ferric reducing antioxidant power in this present study is higher compared to protein hydrolysate of fried herring (Clupea harengus), which was found to be 3 µmol Trolox equivalents/g [88]. However, in a recent study [89] on protein isolates of orange-footed sea cucumber (Cucumaria frondosa), the Trolox equivalents exhibited 80-530 µmol /g. The reason for this difference is probably due to the isolation of peptides, resulting in a higher concentration [89,90], compared to the hydrolysates obtained from the present study.…”
Section: Antioxidative Capacity Measured By Frap Abts Dpph and Orac A...contrasting
confidence: 77%
See 1 more Smart Citation
“…In addition, the ferric reducing antioxidant power in this present study is higher compared to protein hydrolysate of fried herring (Clupea harengus), which was found to be 3 µmol Trolox equivalents/g [88]. However, in a recent study [89] on protein isolates of orange-footed sea cucumber (Cucumaria frondosa), the Trolox equivalents exhibited 80-530 µmol /g. The reason for this difference is probably due to the isolation of peptides, resulting in a higher concentration [89,90], compared to the hydrolysates obtained from the present study.…”
Section: Antioxidative Capacity Measured By Frap Abts Dpph and Orac A...contrasting
confidence: 77%
“…However, in a recent study [89] on protein isolates of orange-footed sea cucumber (Cucumaria frondosa), the Trolox equivalents exhibited 80-530 µmol /g. The reason for this difference is probably due to the isolation of peptides, resulting in a higher concentration [89,90], compared to the hydrolysates obtained from the present study. The exhibited DPPH scavenging activities of freeze-dried raw material and all hydrolysates were comparable to previous studies [21,49,93].…”
Section: Antioxidative Capacity Measured By Frap Abts Dpph and Orac A...mentioning
confidence: 95%
“…In addition, sea cucumbers are known to contain various bioactive compounds, such as polysaccharides, collagen and peptides, sphingoids, phenolics, triterpene glycosides (saponins), sterols, carotenoids, and chondroitin, which exhibit various biological and pharmacological functions such as antimicrobial, antioxidant , antihypertensive, immunoregulatory, anti-inflammatory, anticoagulant, anticancer, antidiabetic, antifatigue, antiaging, and antithrombotic which can be seen in Figure 3 (Suwanmala et al, 2016;Shahidi, 2020, 2022;Yu et al, 2020;Q. Wang et al, 2021;Senadheera et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive compounds contained in sea cucumbers include saponins, phenolics, proteins (peptides), carotenoids and lipids (Hossain, Dave and Shahidi, 2020). Based on research, it has been reported that the phenolic compounds in sea cucumbers act as antioxidants which can prevent or reduce oxidative stress in cells, prevent aging and play an important role in controlling various diseases, especially cardiovascular disease, inflammation and cancer Senadheera et al, 2023). Phenolics can inhibit the synthesis of proinflammatory cytokines, especially inducible nitric oxide synthase (iNOS), nitric oxide (NO), TNF-α, interleukin-1β (IL-1β), and prostaglandin E2 (PGE2) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, sea cucumbers (e.g., Cucumaria frondosa, Apostichopus japonicus, Cucumaria japonica, and Holothuria forskali) are rich in proteins, lipids, and SPs, namely fucosylated chondroitin sulfate and fucoidan, as well as saponins, phenolic compounds (e.g., phenolic acids and flavonoids), and carotenoids, among others [10,60]. The phenolic compounds, including protocatechuic acid, gallic acid, ellagic acid, p-coumaric acid, catechin, and quercetin, of sea cucumbers have been reported to have inhibitory activities against tyrosinase, α-glucosidase, and the formation of advanced glycation end products (AGEs) as well as LDL cholesterol and DNA oxidation, while protein isolates/peptides derived from C. frondosa showed antioxidant and ACE inhibitory effects [104,105]. Therefore, these echinoderms have been, and continue to be, examined as a source of biologically active compounds.…”
Section: Echinodermsmentioning
confidence: 99%